Optimalisasi Tekanan Kompaksi, Temperatur Dan Waktu Sintering Terhadap Kekerasan Dan Berat Jenis Aluminium Pada Proses Pencetakan Dengan Metalurgi Serbuk - Totok Suwanda (Universitas Muhammadiyah Yogyakarta, 2006)
Powder metallurgy is one of the manufacturing processes. Upon the process, melting process is not necessary to carry out. The powder is subsequently compacted then sintered. These processes can be conducted either separately or simultaneously. However metallurgy processes have not been commonly developed in Indonesia yet. Therefore it is necessary to carry out preliminary research that serves as a basis for developing of further process. The effect of the independent variables of the process on mechanical and physical properties of the product will be examined. The research was conducted by arranging the independent variables which consist of pressure, temperature and sintering period whereas hardness and density of product are the dependent variables. Aluminum will be water atomized for obtaining the powder. Response surface method is used as the experimental design method. The method can show the effect of the independent variables individually and the interaction among the variables. Data analysis will result mathematic formula showing the functional relation. The research concludes that 170 MPa compaction pressure and 500 0C sintering temperature and 40 to 50 minutes range period of sintering produces the maximum Brinell hardness number of 47 BHN. On the other hand, the effect of the independent variables to the density has not been able to be formulated.